Análise de fatores motivacionais de trabalhadores do segmento de tecnologia do sul do brasil pela Multidimensional Work Motivation Scale (MWMS) - Machado, Clarice Lucas da Silva (Universidade do Vale do Rio dos Sinos, 2016)
This field study, which used a quantitative and qualitative approach, was carried out by 262 employees of technology companies in South Brazil. The main objective was to analyze motivational factors in the work environment of workers in this particular sector. Based on the Multidimensional Work Motivation Scale (MWMS), participants were sent electronic surveys using the “Snowball Sampling” technique. The study was conducted using six (6) semi-structured interviews by way of content analysis technique. As a result, it was observed that these workers are primarily guided by Autonomous Motivation, followed by Controlled Motivation. Please note that the study did not focus on demotivation factors of the workers. Connecting personal feelings with personal values, such as feelings of autonomy and competence, as well as the motivation to learn, is presented as strong features of these professionals, in which they value relationships at work at all levels and are encouraged by a sense of psychological freedom. They like to compete and solve complex problems, are motivated by feelings of high self-esteem, social and professional self-perception, as well as being recognized for their skills. The study reveals a profile that needs to feel competent, that seeks to overcome others and himself, or better yet, be recognized beyond institutional constraints. It is recommended that motivation be worked through an organizational context, both through leadership and the individual, jointly covering more elements that will leverage the worker’s well-being and consequently improve organizational results.
Keywords: Motivação; Profissionais de Tecnologia; Escala MWMS (Multidimensional Work Motivation Scale); Gestão de pessoas; Motivation; Technology professionals; MWMS Scale (Multidimensional Work Motivation Scale); People management; ACCNPQ::Ciências Sociais Aplicadas::Administração